Characterization of Fusarium venenatum Mycoprotein-Based Harbin Red Sausages - Xue-Li Li; Xian-Ni Qi; Jia-Chen Deng; Ping Jiang; Shu-Yuan Wang; Xing-Li Xue; Qin-Hong Wang; Xiaoqing Ren (Foods)
Fusarium venenatum mycoprotein is an alternative, nutritious protein source with a meat-like texture. Here, F. venenatum mycoprotein-based Harbin red sausage was developed and characterized. The study focused on the effect of mycoprotein on the quality of red sausages, which were evaluated in five groups of red sausages based on nutrient content, differential scanning calorimetry (DSC), and gas chromatography–ion mobility spectrometry (GC-IMS). The results showed that increasing the component of mycoprotein in red sausage increased the protein and volatile organic compound content but decreased the water and ash content. There was no significant difference (p > 0.05) between red sausage with 25% added mycoprotein and traditional red sausage in terms of redness and thawed water component, but the protein component was higher, the flavor substances were slightly richer, and the consumer preference was higher. These results suggest that moderate amounts of mycoprotein can improve nutritional value and maintain sensory quality, but that higher levels of substitution can adversely affect preference. This study highlights the potential of mycoprotein as an artificial meat that can strike a balance between improved nutritional value and sensory acceptability.